2020
DOI: 10.1186/s12904-020-00652-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in perspectives of pediatricians on advance care planning: a cross-sectional survey

Abstract: Background The increase in the number of pediatric patients with complex health conditions necessitates the application of advance care planning for children. Earlier, withdrawal of life-sustaining treatment was taboo in the medical society in South Korea due to the history of such practice being punishable by law, and physicians tended to pursue aggressive treatment. With changes in public opinion on end-of-life care, the Korean government enacted a new law that protect human dignity by respecting patients’ s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Even parents who had not been told that their child’s condition was life‐limiting or who had not had previous ACP discussion found the ACP discussion acceptable. This is reflected in past studies that showed parents look to health‐care providers to initiate ACP discussions, 24,25 hence allaying anxiety and fear among clinicians who are hesitant to initiate ACP discussion so as not to ‘upset’ the family 2,18,19,26 . A high acceptance rate of ACP discussion indirectly implies the parents’ readiness to participate in decision‐making exercises related to their child’s health, which is a key factor for successful ACP implementation 4,8,9,14,22 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even parents who had not been told that their child’s condition was life‐limiting or who had not had previous ACP discussion found the ACP discussion acceptable. This is reflected in past studies that showed parents look to health‐care providers to initiate ACP discussions, 24,25 hence allaying anxiety and fear among clinicians who are hesitant to initiate ACP discussion so as not to ‘upset’ the family 2,18,19,26 . A high acceptance rate of ACP discussion indirectly implies the parents’ readiness to participate in decision‐making exercises related to their child’s health, which is a key factor for successful ACP implementation 4,8,9,14,22 …”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in past studies that showed parents look to health-care providers to initiate ACP discussions, 24,25 hence allaying anxiety and fear among clinicians who are hesitant to initiate ACP discussion so as not to 'upset' the family. 2,18,19,26 A high acceptance rate of ACP discussion indirectly implies the parents' readiness to participate in decision-making exercises related to their child's health, which is a key factor for successful ACP implementation. 4,8,9,14,22 Most (89.5%) of the parents in this study felt the timing for ACP discussion was suitable, which is substantiated by recommendations from other studies that support having discussions during clinically stable periods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We conducted a retrospective cohort study of patients referred to the PPC team. In Korea, palliative care was a very unfamiliar concept, and only a few doctors were confident with it [17,18]. Therefore, we assumed that primary care physicians had a lack of knowledge in PPC.…”
Section: Designmentioning
confidence: 99%